Beyond individuals: Toward a "distributed" approach to farmer decision‐making behavior. (9th October 2018) - Rose, David C.; Keating, Connor; Vrain, Emilie; Morris, Carol
Abstract : Here, we address flaws in existing approaches to farmer behavioral change which place undue attention on the individual. Rather, we argue for a more distributed understanding of farmer decision‐making behavior, which includes all relevant actors within a farmers' "ring of confidence" in projects.